Pengembangan E-Book Teori Ekonomi Mikro pada Pembelajaran Berbasis Blended Learning Program Studi Pendidikan Ekonomi IKIP Budi Utomo Malang - Novi Eko Prasetyo; Miftah Rakhmadian; Titik Purwati (IKIP PGRI Bojonegoro, 2019)
Abstract. The micro-economics e-book is one of source of learning for students of economics education program of IKIP Budi Utomo, Malang. The purpose of this e-book is to reconstruct the concepts between the theory and practice presented in each subject matter. The research method used in this research is research and development. This research use the Instructional Design Dick and Carey model. This e-book material consists of 7 subject matters. The results of this study showed that as many as 57 students selected to conduct the assessment gave a 96% value with